Factors that influence acceptance of GM labels on halal food among Muslim consumers - Md Rapi, Nurul Razanah; Kamarulzaman, Nitty Hirawaty; Ismail, Normaz Wana (HH Publisher, 2020)
Genetically modified (GM) foods are produced from the development of modern biotechnology and gene combinations of the same or different species. GM foods have become an important issue among Muslim consumers in consuming halalan toyyiban food produced from GM foods. This in line with the decision of Muslim consumers in the selection of halal food that is closely related to faith, religion, and culture in the Islamic society. Labeling on food packaging is an important indicator of every food product in the market by Muslim consumers to determine the halalness of a food product. Therefore, the objective of this study is to determine factors that influence acceptance of GM labels on halal food among Muslim consumers. By using purposive sampling, 320 Muslim consumers were selected located in Klang Valley, Malaysia. An interviewer-administered questionnaire with the target consumers was carried out to obtain consumers’ responses. Several analyses were employed to analyze the data namely descriptive analysis, Chi-square analysis, Pearson correlation analysis, and factor analysis. The results of this study revealed that the majority of Muslim consumers were not aware of GM labels on halal food. There were significant associations between age, education level, and monthly income and Muslim consumers’ acceptance of GM labels on halal food. The relationship between awareness and acceptance showed a weak positive relationship. This study also revealed labeling characteristics, religious belief, and health concern are the three factors that influenced Muslim consumers’ acceptance of GM labeling on halal food. This study emphasizes that a continuous encouragement to food manufacturers in providing and displaying proper labeling on food products would assist Muslim consumers to enhance their awareness and acceptance of GM labels.